Effects of a Dietary Blend of Essential Oils, Capsaicin, and Yeast Metabolites on Performance, Physiological, Metabolism, and Immune Response of Heat-Stressed Pigs - Campos, Lorena Duarte [UNESP]; Marçal, Danilo Alves; França, Ismael [UNESP]; Silva, Cleslei Alisson [UNESP]; Veira, Alini Mari [UNESP]; Oliveira, Amanda Faria [UNESP]; Fraga, Alícia Zem; de Araujo, Rafael C; Maia, Alex Sandro Campos [UNESP]; Hauschild, Luciano [UNESP] (MDPI, 2025)
This study investigated the effects of a dietary additive composed of compounds derived from essential oils (carvacrol, eugenol, cinnamaldehyde), capsaicin, and yeast metabolites on the performance, body composition, metabolism, and immune status of pigs under chronic heat stress (HS). A total of 24 crossbred gilts (50 ± 3.98 kg) were assigned to one of two diets: a control diet (CON) or the same diet supplemented with the additive blend (2.5 g/kg; BLEND). Animals were housed collectively, with individual feed intake recorded using automatic precision feeders over a 56-day period at a constant ambient temperature of 35 °C. Heat stress increased rectal temperature initially (p < 0.01), which gradually declined over time. No significant differences were found in overall performance or tissue deposition between treatments (p > 0.05), though pigs fed the BLEND diet tended to have an 18% lower fat deposition compared with the CON group (148.3 vs. 121.3 g/d, p = 0.094). The additive had no effect on inflammatory or most biochemical parameters, except for increased creatinine compared with the CON group (1.76 vs. 1.63 mg/dL; p = 0.032) and a tendency for elevated LDH (1064.87 vs. 939.17 U/L; p = 0.075). In conclusion, chronic HS impaired metabolic and immune parameters and altered body composition. The dietary blend did not enhance performance but showed a tendency to reduce lipid deposition under thermal stress conditions. Further studies are needed to elucidate the individual and combined actions of this feed additive in mitigating the impacts of HS on pigs.